Synthesis and characterization of organotin (IV) complexes of tridentate schiff bases containing -ONN/ONS donor atoms - Chiew, Wang See. (Universiti Malaysia Sarawak, (UNIMAS), 2007)
Four organotin(IV) complexes of methyl pyruvate thiosemicarbazone ligand (1) with RnSnC4-n (n 1, 2) have been synthesized in the presence of base and refluxing methanol in 1: I: I mole ratio (metal:base:ligand). Another four organotin(IV) complexes of salicylaldehyde 2-pyridine hydrazone ligand (2) in I: I: 1 mole ratio (metal:base:ligand) have also been synthesized with same method. All organotin(IV) complexes (3-10) have been characterized using CRN analyser, UV-Visible and IR spectral studies. All organotin(IV) complexes (3-10) are non electrolytic in nature. Spectral studies suggested that both the ligands (1-2) act as a mononegative tridentate nature in their organotin(IV) complexes. Therefore, a six coordinated molecular structure has been proposed for all the mentioned organotin(IV) complexes.